2022
DOI: 10.1182/blood.2022015478
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes in ZUMA-7, a phase 3 study of axicabtagene ciloleucel in second-line large B-cell lymphoma

Abstract: Here we report the first comparative analysis of patient-reported outcomes (PROs) with chimeric antigen receptor T-cell therapy versus standard-of-care (SOC) therapy in second-line relapsed/refractory large B-cell lymphoma (R/R LBCL) from the pivotal randomized phase 3 ZUMA-7 (NCT03391466) study of axicabtagene ciloleucel (axi-cel) versus SOC. PRO instruments were administered at baseline, day 50, day 100, day 150, month 9, and every 3 months from randomization until 24 months or an event-free survival event. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 41 publications
3
36
0
Order By: Relevance
“…106,[111][112][113][114] In the randomized trial ZUMA-7, second-line axi-cel was associated with a more rapid recovery of patient-reported quality of life and physical functioning by Day +100 compared to standard of care. 115 Indeed, long-term survivors of CAR-T cell therapy have overall comparable self-reported measures of mental health, fatigue, and social function as the general population. 41 Nevertheless, anxiety, depression, and other stressors continue to afflict a substantial proportion of long-term survivors, 41,106 underscoring the importance of screening and support for mental health disorders as part of routine care.…”
Section: Psychosocial Effectsmentioning
confidence: 99%
“…106,[111][112][113][114] In the randomized trial ZUMA-7, second-line axi-cel was associated with a more rapid recovery of patient-reported quality of life and physical functioning by Day +100 compared to standard of care. 115 Indeed, long-term survivors of CAR-T cell therapy have overall comparable self-reported measures of mental health, fatigue, and social function as the general population. 41 Nevertheless, anxiety, depression, and other stressors continue to afflict a substantial proportion of long-term survivors, 41,106 underscoring the importance of screening and support for mental health disorders as part of routine care.…”
Section: Psychosocial Effectsmentioning
confidence: 99%
“…Prespecified hypotheses for PRO domains [EORTC QLQ-C30 Physical Functioning, EORTC QLQ-C30 Global Health Status/QoL, and EQ-5D-5L visual analog scale (VAS)] were tested as previously reported (24,25). A mixed-effects model with repeated measures at day 100 and at subsequent time points conditional on statistical significance at the previous time point was used.…”
Section: Translational Relevancementioning
confidence: 99%
“…Safety analyses included randomized patients ≥65 years who received axicel or ≥1 dose of SOC therapy per protocol, analyzed by protocol therapy received. The QoL subgroup included patients ≥65 years who had a baseline PRO and ≥1 post-baseline measure completed (24,25).…”
Section: Translational Relevancementioning
confidence: 99%
“…CAR-T cell-treated patients report dramatic changes in HRQOL related to the cumulative benefit of CAR-T cells on disease control and of the short and long-term toxicities from the cellular treatment [ 19 , 20 ]. The estimate of HRQOL can be translated into a utility score to reflect the level of physical, mental, and social functioning associated with a particular health state and be incorporated into the economic evaluation.…”
Section: Uncertainty Around Clinical Benefitmentioning
confidence: 99%
“…So far, most studies have demonstrated improvement in HRQOL with CAR-T cell treatment in patients with r/r DLBCL, but the results published so far lack validity for patients who receive publicly funded CAR-T therapy in Canada, since only patients with aggressive B-cell lymphoma who are either primary refractory or who have relapsed after two lines of therapy are eligible for CAR-T reimbursement. [ 19 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Uncertainty Around Clinical Benefitmentioning
confidence: 99%